Productive indicators of lambs in native grasslands, supplemented with Acacia cochliacantha, in the dry tropic of Guerrero, Mexico - Mireles, E. J.; Rodríguez, D.; Jordán, H.; Ramírez, Aurora H.; García, Águeda; Gutiérrez, I. (Cuban Journal of Agricultural Science, 2016)
In order to quantify some productive indicators and the botanical composition of diets for lambs, supplemented with ground and whole pods of Acacia cochliacantha, related to the requirements of dry matter intake, 60 Pelibuey-Black Belly x Dorper-Katadhin lambs were used, with 20.4 ± 2.1 kg of LW, divided by a completely at random experimental design, with six treatments. During the dry period, the treatments were: grazing (Pas), grazing plus 15 % of supplementation with ground pods (Pas 15), and grazing plus 30 % of supplementation with ground pods (Pas 30) for 105 d. During the rainy period, the treatments were: grazing (Past), grazing plus 30 % of ground pods (Past 30M), and grazing plus 30 % of whole pods (Past 30E) for 84 d. The daily weight gain was determined every 21 d. At the end of this study, six animals of each group were slaughter to determine hot carcass yield, and register the weight of some viscera, and pericardial and perirenal fat. The analysis of variance and the test of Duncan (P < 0.05) were applied to the data. During the dry period, the daily weight gain was 68, 59 and 63 g, and the hot carcass yield was 37.09, 37.85 and 39.10 % for grazing, grazing plus 15 % of supplementation with ground pods, and grazing plus 30 % of supplementation with ground pods, respectively. During the rainy period, the gain was 120, 105, and 113 g, and the yield was 40.51, 42.02 and 40.10 % for grazing, grazing plus 30 % of supplementation with ground pods, and grazing plus 30 % of supplementation with whole pods, respectively. It can be concluded that the botanical composition of the diets for lambs was similar during both seasons. Irrigated native grasslands produced less daily weight gain and hot carcass yield during the dry season than during the rainy period. The supplementation with ground or whole pods of Acacia cochliacantha had no influence on the studied indicators.Key words: lambs, native grasslands, productive indicators.